Abutasterone, an ecdysone from abuta velutina - Pinheiro, Maria Lucia B.; Filho, Wilson W.; Rocha, Arnaldo Imbiriba da; Porter, Barry; Wenkert, Ernest T. (Phytochemistry, 1983)
The ecdysone abutasterone has been isolated from the Amazonian plant Abuta velutina and its structure elucidated by spectral means. © 1983.